2016
DOI: 10.1039/c6cp04418b
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the kinetically trapped i-motif DNA intermediates

Abstract: In the present work, the conformational dynamics and folding pathways of i-motif DNA were studied in solution and in the gas-phase as a function of the solution pH conditions using circular dichroism (CD), photoacoustic calorimetry analysis (PAC), trapped ion mobility spectrometry - mass spectrometry (TIMS-MS), and molecular dynamics (MD). Solution studies showed at thermodynamic equilibrium the existence of a two-state folding mechanism, whereas during the pH = 7.0 → 4.5 transition a fast and slow phase (ΔHfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 104 publications
7
54
0
Order By: Relevance
“…However, the CCS profile of the unfolded structure is very sensitive to the NH4OAc concentration, even though the solution NMR spectra are the same: at 15 mM NH4OAc, the 6-ion conformations are more compact; at 100 mM NH4OAc, only an extended form (CCS = 897 Ų) is observed. Note that the previous study Fernandez-Lima and collaborators [34], who found no marked effect of the pH on the ion mobility of 21C, had been carried out in 10 mM NH4OAc, so our results are consistent with theirs.…”
Section: Ion Mobility Spectrometry Of the 21-mer I-motif And Its Contsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the CCS profile of the unfolded structure is very sensitive to the NH4OAc concentration, even though the solution NMR spectra are the same: at 15 mM NH4OAc, the 6-ion conformations are more compact; at 100 mM NH4OAc, only an extended form (CCS = 897 Ų) is observed. Note that the previous study Fernandez-Lima and collaborators [34], who found no marked effect of the pH on the ion mobility of 21C, had been carried out in 10 mM NH4OAc, so our results are consistent with theirs.…”
Section: Ion Mobility Spectrometry Of the 21-mer I-motif And Its Contsupporting
confidence: 92%
“…We showed previously by IRMPD ion spectroscopy that electrosprayed i-motif structures preserved the C-H + -C base pairs, at least for low charge states (4-to 6-) [33]. However, Fernandez-Lima and collaborators had found no difference in ion mobility profiles of the human telomeric i-motif sequence d(CCCTAA)3CCC in 10 mM NH4OAc as a function of the pH [34], casting doubt on the potential utility of ESI-IMS-MS to study i-motif solution folding. Here, we show that the ion mobility spectra depend strongly on the electrolyte (NH4OAc) concentration used for electrospray, and we show the importance of control experiments (different pH, NH4OAc concentrations, activation energies, and experiments with control sequences) to infer information on the solution structures from ion mobility measurements.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In separate but related studies, Garabedian et . al and coworkers used photoacoustic calorimetry analysis (PAC) with trapped ion mobility spectrometry (TIMS)-MS to study structural transformations of i-motif DNA resulting from pH changes [59]. Boschmans et .…”
Section: Introductionmentioning
confidence: 99%
“…8392 More recently, with the development of trapped ion mobility spectrometry (TIMS), 9395 several reports have shown the potential of TIMS-MS to decouple the mobility (K) separation from the MS analysis time for fast, gas-phase separation and for molecular structural elucidation. 51, 93, 96117 In particular, the advantages of TIMS over traditional IMS analyzers has been shown for fast screening 96 and targeted 79 analysis of molecular ions from complex chemical mixtures; the study of isomerization kinetics of small molecules, 98 peptides, DNA, proteins and their complexes in the absence of the bulk solvent; 99103 the influence of the collision partner on the molecular structure; 104 and the factors that affect molecular-adduct complex lifetime and stability during TIMS measurements. 105 A significant feature to note is the high resolving power of TIMS analyzers (R TIMS up to 400 107 ) and accuracy in measuring ion-neutral collision cross section (CCS, <0.6% error).…”
Section: Introductionmentioning
confidence: 99%